Potential pollution risks of historic landfills on low‐lying coasts and estuaries. (16th November 2017) - Brand, James H.; Spencer, Kate L.; O'shea, Francis T.; Lindsay, John E.
Abstract : Historically, it was common practice to dispose of landfill waste in low‐lying estuarine and coastal areas where land had limited value due to flood risk. Such 'historic landfills' are frequently unlined with no leachate management and inadequate records of the waste they contain. Globally, there are 100, 000s such landfills, for example, in England there are >1200 historic landfills in low‐lying coastal areas with many in close proximity to designated environmental sites or in/near areas influencing bathing water quality; yet, there is a very limited understanding of the environmental risk posed. Hence, coastal managers are more likely to select conservative management policies, for example, hold‐the‐line, when alternative more sustainable policies, for example, managed realignment, may be preferred. Some historic coastal landfills have already started to erode and release waste, and with the anticipated effects of climate change, erosion events are likely to become more frequent. Strategies to mitigate the risk of contaminant release from historic landfills such as excavation and relocation or incineration of waste would be prohibitively expensive for many countries. Therefore, it will be necessary to identify which sites pose the greatest pollution risk in order that resources can be prioritized, and to develop alternative management strategies based on site specific risk. Before such management strategies can be achieved there remain many unknowns to be addressed including the extent of legacy pollution in coastal sediments, impacts of saline flooding on contaminant release and the nature, behavior and environmental impact of solid waste release in the coastal zone. WIREs Water 2018, 5:e1264. doi: 10.1002/wat2.1264 This article is categorized under: Engineering Water > Sustainable Engineering of Water Science of Water > Water and Environmental Change Abstract : This paper highlights historic landfills in low‐lying estuarine and coastal locations (historic coastal landfills) as potential sources of diffuse pollution. It reviews what is known about contaminants in the landfills, and considers contaminant pathways and likely receptors. It identifies significant gaps in knowledge and a need for further research.